The influence of corticosteroids on hemostasis in healthy subjects - Majoor, C. J.; Sneeboer, M. M. S.; Kievit, A.; Meijers, J. C. M.; Poll, T.; Lutter, R.; Bel, E. H.; Kamphuisen, P. W. (Journal of thrombosis and haemostasis, 2016)
Essentials Corticosteroids are associated with venous thromboembolism in patients with inflammatory diseases. Healthy subjects received 0.5 mg kg−1 of prednisolone or placebo for 10 days in a randomized study. von Willebrand factor, plasminogen activator type 1 and in vitro thrombin generation were enhanced. Corticosteroids may contribute to the thromboembolic risk in patients with inflammatory diseases. Summary Background Corticosteroids have been associated with an increased risk of venous thromboembolism in patients treated for inflammatory diseases. It is unclear whether the thrombotic risk is induced by the inflammation of the underlying inflammatory diseases or whether corticosteroids are prothrombotic as well. Considering the widespread use of corticosteroids in clinical practise, it is critical to know whether corticosteroids enhance coagulation. Objective To investigate whether a 10‐day prednisolone burst therapy activates hemostasis in healthy individuals. Methods Healthy subjects received either 0.5 mg kg−1 day−1 of oral prednisolone or placebo. Venous blood was collected at baseline, day 1 and day 10 and tested for thrombin‐antithrombin complexes (TATc), D‐dimer, plasmin‐alpha2‐antiplasmin complexes (PAPc), plasminogen‐activator inhibitor type‐1 (PAI‐1), von Willebrand factor (VWF) and thrombin generation (peak thrombin, velocity index and endogenous thrombin potential [ETP]). Results Fifteen subjects received prednisolone and 16 placebo (median age 29 vs. 22 years, female subjects 33% vs. 56%, respectively). Peak thrombin and velocity index were higher in the placebo group at baseline. After 10 days of treatment, peak thrombin, velocity index, PAI‐1 and VWF increased in the oral prednisolone group as compared with the placebo group (15.8 [SD 16.3] vs. −0.1 [SD 16.1], 41.2 [SD 41.3] vs. −2.3 [SD 42.7], 18.0 [IQR 8.0–37.0] vs. 0.5 [IQR −18.5–13.0], 4.0 [IQR −1.0–12.0] vs. 0.0 [IQR −2.5–1.5], respectively). No changes were observed for TATc, ETP, PAPc and D‐dimer. Conclusions Oral prednisolone induces a procoagulant state in healthy subjects, suggesting that corticosteroid treatment may increase the thromboembolic risk in patients with inflammatory diseases.